1991
DOI: 10.1007/bf00132289
|View full text |Cite
|
Sign up to set email alerts
|

Course design, teaching method and student epistemology

Abstract: Previous research into student learning in departments of higher education has shown that links can be established between students' approaches to studying and their perceptions of the academic environment. It has also been found that students with differing study orientations are likely to define effective teaching in ways which reflect those orientations. The study reported here began by identifying different types of student epistemology and then investigated those factors within the academic environment wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 11 publications
1
28
0
4
Order By: Relevance
“…The findings for the HK group were consistent with those of previous studies (Gow and Kember, 1993;Trigwell, Prosser, and Taylor, 1994;Sheppard and Gilbert, 1991): teacher-centered approaches (transferring and shaping) encourage students to adopt a surface learning approach, and student-centered approaches (traveling and growing) are correlated with a deep learning approach (see Table 9). The study also revealed that the HK students' preferred learning approach (achieving motivation and surface strategy) (Leung, Ng, and Li, 2004) is affected by the transferring, shaping,…”
Section: Observationssupporting
confidence: 91%
See 1 more Smart Citation
“…The findings for the HK group were consistent with those of previous studies (Gow and Kember, 1993;Trigwell, Prosser, and Taylor, 1994;Sheppard and Gilbert, 1991): teacher-centered approaches (transferring and shaping) encourage students to adopt a surface learning approach, and student-centered approaches (traveling and growing) are correlated with a deep learning approach (see Table 9). The study also revealed that the HK students' preferred learning approach (achieving motivation and surface strategy) (Leung, Ng, and Li, 2004) is affected by the transferring, shaping,…”
Section: Observationssupporting
confidence: 91%
“…Sheppard and Gilbert (1991) and Gow and Kember (1993) found that the development of student epistemology was influenced by both the students' learning approaches and their perceptions of their learning environment (i.e., teaching orientation). Literature suggests a relationship between teaching orientations, teaching approaches, and student learning.…”
Section: April 2008mentioning
confidence: 97%
“…Además, se detecta asociación entre las creencias epistemológicas y las creencias sobre el aprendizaje (Brownlee, 2001;Sheppard y Gilbert, 1991), de ahí que las creencias estén asociadas con los enfoques y los resultados del aprendizaje. Así, las creencias relativistas/sofisticadas están relacionadas con el enfoque profundo o transformativo y la reflexión metacognitiva.…”
Section: Factores Del Estudianteunclassified
“…Alanyazın incelendiğinde bu bulgunun alanyazınla kısmen örtüştüğü görülmektedir. Özellikle öğretmen ve öğretme yöntemi ile öğrencilerin öğrenme yaklaşımları arasındaki ilişkiyi sistematize etme adına Trigwell, Prosser ve Taylor (1994, s. 78-83), Sheppard ve Gilbert (1991), Trigwell, Prosser ve Waterhouse (1999, s. 60) ve Elstad, Christophersen ve Turmo (2012) çalışmalar yapmış ve bu çalışmalarda öğretme yaklaşımları ile öğrencilerin öğrenme yaklaşımları arasında ilişki olduğu da ifade edilmiş ve öğretmen merkezli yaklaşımlarla yüzeysel öğrenme yaklaşımı arasında öğrenci merkezli yaklaşımlarla derinlemesine öğrenme yaklaşımı arasında bir ilişki olduğu belirlenmiştir. Bu bağlamda üniversite sınavında yüzde bir dilimde olan başarılı ve başarıya odaklanmış öğrencilerin çalışma yaklaşımlarının öğretmenlerin kullandıkları öğretme yöntemleri tarafından etkilenmediklerini ifade etmeleri etkili öğrenme kapsamında, öğrencilerin hedeflerini belirlemiş ve kendi öğrenmelerinin sorumluluğunu üstlenen öz-düzenleyici öğrenenler olmalarından sınav ve başarı odaklı çalışmayı merkeze almış olmalarından kaynaklanabilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified